Impelementasi Layanan Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatan kesadaran Anti -Bullying pada Siswa Kelas IX G SMP 5 Kudus - Isna Alfiatussa'adah; Indah Lestari; Julia Wijayanti (Journal of Innovative and Creativity, 2025)
Bullying is a common issue in schools and can negatively impact students' psychological development. This study aims to enhance anti-bullying awareness among ninth-grade students at SMP 5 Kudus through group counseling services using the role-playing technique. The research employed a Guidance and Counseling Action Research (Penelitian Tindakan Bimbingan dan Konseling – PTBK) method based on the Kemmis and McTaggart model, consisting of two cycles. Each cycle included the stages of planning, implementation, observation, and reflection. The findings indicate that before the intervention, students' anti-bullying awareness was categorized as moderate, with an average score of 78.4%. After the implementation of Cycle I, the score increased to 90.9%, and further improved in Cycle II, reaching 105.1%, which falls into the high category. The role-playing technique proved effective in raising students' awareness of bullying, as it allowed them to understand the victim’s feelings and the consequences of bullying behavior through direct experience. This study recommends the continuous implementation of group counseling programs with the support of teachers, homeroom teachers, and parents to create a safer and bullying-free school environment.